São Paulo International Architectural Biennales: Notes for a Retrospective View of the Turn of the Millennium - Tavares Rosalino, Alisson (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2020)
This article aims to contribute to an understanding of the role played by major architectural exhibitions, in this case the São Paulo International Architectural Biennale (BIA), as spaces for the formation of networks and transnational dialogues, along with promoting featured architects, which would assume a more prominent role in later periods. The fourth BIA, held in 1999, represented a pivotal moment that would guide architectural production and debates in the new millennium.